Implementation of Public Educational Policies for the Inclusion of Persons with Disabilities in Professional Education: CEFET-RN and TEC NEP Action (Research, Society and Development, 2018)
At the same time as the change in the institutional structure of the Federal Technical School of Rio Grande do Norte (ETFRN), for the Federal Center of Technological Education of Rio Grande do Norte (CEFET-RN), the TEC NEP action - Education, Technology and People with Special Educational Needs (BRASIL, 2000). In this scenario, this paper aims to present institutional actions carried out under the CEFET-RN, in line with the guidelines of the TEC NEP Program in the period between 1999 and 2007. This is an exploratory survey conducted by of documentary analysis and bibliographical review from the studies of Cunha (2016) and Musse (2005). TEC NEP emerge on the national scene in order to carry out the proposal for education for all (UNESCO, 1994) providing opportunities for the inclusion of students with disabilities, also in the Federal Professional Education Network. As a result of this research, it is possible to highlight the promotion of periodic events and formative activities such as the Continuing Teacher Education Program for an inclusive educational system and the training course for inclusive methodological strategies. Thus, institutional actions involving the school community in discussing issues related to the inclusion of Persons with disabilities in CEFET-RN, in line with the main objectives of the TEC NEP Program, became evident even before implementation at the national level.